Implementation of Closing and Disbursement of the International Travel Insurance Policy in Relation with COVID-19 Disease - Tanjung, Kurnia Togar Pandapotan; Yumna, Athaya; Shanty, Janthi Dharma (UI Scholars Hub, 2024)
In life, one is always faced with uncertain risks. In the case of the COVID-19 pandemic, a person traveling abroad for business or tourism purposes has the risk of being infected with COVID-19. One of the efforts that one can make to minimize the risk of being infected with the COVID-19 is to transfer the risk to the Insurer by registering with an Insurance Company to get a Travel Insurance. The COVID-19 International Travel Insurance provides a guarantee of protection to someone traveling internationally from the risk of being infected with the COVID-19 so that the trip becomes comfortable, safe, and without worry. The issues to be discussed in this study include the form of liability of the Insurer to the Insured who is infected with COVID-19 and the process of claiming the COVID-19 International Travel Insurance. The purpose of conducting this research is to find out how the accountability of the Insurer to the Insured who is infected with COVID-19 is executed, and how the process for claiming COVID-19 International Travel Insurance is conducted. The analytical method used in this thesis is qualitative analysis which aims to determine the importance of clause specifications on Travel Insurance Policies, as well as the importance of writing the Insurance Policies using words, phrases, and sentences that are clear and easily understood by the prospective Insured so that there are no differences in interpretation. The results of the research conducted by the author produce conclusions in the form of as follows: 1. The coverage benefits that will be provided by the Insurer to the Insured who is infected with COVID-19 will be provided in accordance with what is stated in the COVID-19 International Travel Insurance Policy clause. However, in the Insurance Policy, there is no clause that clearly and in detail explains the limits of coverage that will be borne by the Insurer; 2. The insured who tests positive for COVID-19 while traveling abroad can submit the COVID-19 International Travel Insurance claim to the Insurer. The stages of filing a claim consist of reporting to the Insurance Company while still in the territory of the insured country, filling out a claim form, and preparing claim documents and supporting documents.